¿Qué espera el profesorado de secundaria de las actividades científicas no formales? - Martín-García, Jorge; Dies Álvarez, María Eugenia (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2024)
Abstract: This article presents a four-year longitudinal study analysing what teachers who participate in a non-formal scientific activity think they will learn during the activity. Unlike previous studies, this paper is focused on a long-term activity. The answers given by the teachers to an open-ended question were subjected to an interpretative-descriptive analysis which allowed the emergence of five main categories of response and five teacher profiles. These categories and profiles allowed the characterization and interpretation of teachers’ responses. It is concluded that the teachers perceive the activity as a multidisciplinary training opportunity with which to expand and diversify their formation and, especially, to acquire new teaching-learning strategies that can be transferred to their classrooms. Keywords: Non-formal education; teacher training, secondary education; teachers’ expectations.